High prevalence and mortality due to Histoplasma capsulatum in the Brazilian Amazon: An autopsy study. - Natalia Rakislova; Juan Carlos Hurtado; Antonio E M Palhares; Luiz Ferreira; Monique Freire; Marcus Lacerda; Wuelton Monteiro; Mireia Navarro; Isaac Casas; Marcus de Melo Teixeira; Paola Castillo; Maria Teresa Rodrigo-Calvo; et al. (Public Library of Science (PLoS), 2021)
Background Histoplasmosis is acquired by inhalation of spores of the dimorphic fungus Histoplasma spp. Although this pathogen is distributed worldwide, it is more prevalent in the Americas. However, the real burden of histoplasmosis remains undefined in many endemic regions. Methodology We conducted a series of 61 autopsies to individuals who died in a hospital in the Brazilian Amazon focused on infectious diseases. We performed a detailed histological and microbiological evaluation with genetic characterization of Histoplasma strains with the aim to evaluate the contribution of histoplasmosis to morbidity and mortality. Additionally, we assessed the clinicopathological correlation. Principal findings Evidence of Histoplasma infection was detected in 21 patients (34%). Eight cases were disseminated infections, all of them occurred in HIV-positive patients. Six cases were localized histoplasmosis, limited to the lungs. In seven patients Histoplasma DNA was detected by PCR in patients with no histological lesions. Histoplasma infection was detected in 38% of HIV-positive patients and was a major contributor to death in 22% of them. Lungs, liver and spleen were affected in all cases of disseminated histoplasmosis. Phylogenetic analysis of the strains suggested a high diversity of Histoplasma species circulating in the Brazilian Amazon. Histoplasmosis was clinically missed in 75% of the disseminated infections. Conclusions The high incidence of histoplasmosis, the low index of clinical suspicion, and the severity of the disseminated disease highlight the need of proactively implementing sensitive routine screening methods for this pathogen in endemic areas. Antifungal prophylaxis against Histoplasma should be encouraged in the severely immunocompromised HIV patients in these areas. In conclusion, substantial mortality is associated with disseminated histoplasmosis among HIV-positive patients in the Brazilian Amazon.